1997
DOI: 10.1139/f97-090
|View full text |Cite
|
Sign up to set email alerts
|

Riverine salmonid egg burial depths: review of published data and implications for scour studies

Abstract: Published data on salmon, trout, and charr egg burial depths are highly variable and inconsistent. Primary sources of variation include elevation datum and portion of the egg pocket referenced to; differences in spawning behavior and the number, thickness, and location of egg pockets; relationships between egg depth, fish species, and corresponding size of female and spawning substrate and velocity characteristics; sampling method; presence of excavation barriers; redd superimposition; and scour and fill by hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(50 citation statements)
references
References 35 publications
1
49
0
Order By: Relevance
“…Fry, around the time of emergence, is considered to be the live stage most sensitive to high floods (Jensen and Johnsen 1999;Cattanéo et al 2002;Tetzlaff et al 2005) whereas egg scouring is thought to occur only with extreme events (Cattanéo et al 2002). However, only a slight increase in discharge could result in significant egg damage (Montgomery et al 1996) and high discharges during incubation time and emergence was found to be inversely related to year-class-strength of brown trout (DeVries 1997;Spina 2001;Cattanéo et al 2002). As scouring is, besides discharge, dependent on gravel size and bedform roughness (Montgomery et al 1996;Lapointe et al 2000) critical discharge is different for each stream.…”
Section: Effect Of Changes In Temperatures and High Discharge On Spawmentioning
confidence: 99%
See 1 more Smart Citation
“…Fry, around the time of emergence, is considered to be the live stage most sensitive to high floods (Jensen and Johnsen 1999;Cattanéo et al 2002;Tetzlaff et al 2005) whereas egg scouring is thought to occur only with extreme events (Cattanéo et al 2002). However, only a slight increase in discharge could result in significant egg damage (Montgomery et al 1996) and high discharges during incubation time and emergence was found to be inversely related to year-class-strength of brown trout (DeVries 1997;Spina 2001;Cattanéo et al 2002). As scouring is, besides discharge, dependent on gravel size and bedform roughness (Montgomery et al 1996;Lapointe et al 2000) critical discharge is different for each stream.…”
Section: Effect Of Changes In Temperatures and High Discharge On Spawmentioning
confidence: 99%
“…After hatching, young alevin remain in the gravel until the yolk sac is used up and they emerge as 'fry' from the gravel. In case of severe riverbed clogging before spawning, eggs are either not spawned (Ortlepp and Murle 2003;Mathisen 1955in DeVries 1997 or insufficiently covered by gravel, with an increased risk for wash out with high floods (Everest et al 1987in DeVries 1997. As fines are usually transported downstream by currents during redd construction, the initial percentage of fines in the redd is often reported to be lower (e.g.…”
Section: Habitat Requirements Of Gravel-spawning Brown Troutmentioning
confidence: 99%
“…Excess bedload including fine and coarse sediments may bury redds, reducing water quality and entombing juvenile salmonids as they attempt to emerge (Lapointe et al 2000). Scour destroys redds, washing eggs downstream DeVries 1997;Lapointe et al 2000). Future study of chum salmon population decline and restoration alternatives in the Grays River should include identification of the nature, location, and extent of 1) successful chum salmon production and 2) threats to incubation success.…”
Section: 50mentioning
confidence: 99%
“…A considerable amount of work has been conducted to determine factors that influence spawning site selection in salmonids. These factors include substrate size (Kondolf and Wolman 1993;Shepherd et al, 1986), stream slope (Montgomery et al, 1999), stream scouring (DeVries, 1997;Tripp and Poulin, 1986), stream velocity (Quinn, 2005), fine sediment Scrivener and Brownlee, 1989), dissolved oxygen (Chapman, 1988;Alderdice et al, 1958, Einum et al, 2002, and cover features, such as overhanging vegetation, woody debris, undercut banks, or small tributaries (Quinn, 2005).…”
Section: Bailey Fisheries and Oceans Canada Personal Communication)mentioning
confidence: 99%
“…Surface features not included in the traditional models such as slope and the associated potential for streambed scouring (Montgomery et al, 1999;DeVries, 1997;Tripp and Poulin, 1986) have also been shown to influence spawning site selection. Habitat features such as overhanging vegetation, woody debris, undercut banks, or small tributaries 29 have also been found to influence spawning site selection (McMahon et al, 1996).…”
Section: Introductionmentioning
confidence: 99%